ANALISIS RESEPSI GEN Z TERHADAP WACANA CHILDFREE DALAM KONTEN INFLUENCER GITASAV (STUDI TEORI RESEPSI STUART HALL) - Maulidiah Jamal, Nurfadhilah; Syarif, Ahmad; Alim, Irwan (Journal of Media and Communication Studies, 2025)
The childfree phenomenon, defined as a conscious decision not to have children, has sparked public debate, especially after influencer Gita Savitri Devi (Gitasav) openly expressed her views on social media. Generation Z, who grew up in the digital era, represents an interesting group to study because they have extensive access to information and are accustomed to shaping opinions through social media platforms. This research aims to analyze Gen Z’s reception of the childfree discourse in Gitasav’s content using Stuart Hall’s reception theory, which categorizes audience responses into three positions: dominant hegemonic position, negotiated position, and oppositional position. The study employs a qualitative approach with the reception study method. Data were collected through in-depth interviews with five Gen Z informants who are students of Universitas Muhammadiyah Makassar. The results show that Gen Z’s reception is divided into three main positions: (1) full acceptance of the childfree perspective as a form of individual freedom (dominant position), (2) selective acceptance by aligning it with cultural and religious values (negotiated position), and (3) complete rejection based on religious norms and social traditions (oppositional position). Factors such as religious background, cultural values, personal experiences, and the intensity of social media exposure influence the formation of these receptions. Keywords: Childfree, Generation Z, Reception, Gitasav, Stuart Hall